The Effect of Lemon Hydrotherapy on Blood Pressure of the Elderly with Hypertension in Karang Jaya Sub-district, Gandus Regency, Palembang - Ardianty, Septi; Ardianty, Septi (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension is a process of compiling individuals who increase blood pressure under normal or chronic conditions. About 60% of the elderly will experience hypertension after successfully 75 years. This is the impact of degeneration that occurs in people who are getting older. Management of advanced hypertension can be done with lemon hydrotherapy. Lemon hydrotherapy is an alternative therapy for relaxation that combines comfort with blood circulation and blood thinners. Lemon hydrotherapy against blood pressure with hypertension in Karang Jaya District, Gandus Regency, Palembang. The method in this study was quantitative, comparative analytical pretest-posttest design (pre-experimental design), the population of all the elderly in Karang Jaya District, Gandus Regency in Palembang as much as 280 further by using a purposive sampling technique obtained a sample of 52. The study was conducted on May-April 2019 in Karang Jaya Sub-district, Gandus Regency, and Palembang. This study shows the average systolic pressure after administration of lemon hydrotherapy by 150.51 mmHg and diastolic blood pressure by 91.03 mmHg. This shows a decrease in blood pressure after being given an intervention with ρ = 0.001. With a 95% confidence interval and a p value of 0,000 (p value < 0.05) showing a decrease in blood pressure before and after lemon hydrotherapy. In conclusion, lemon hydrotherapy has an influence on blood pressure in hypertension in Karang Jaya District, Gandus Regency, and Palembang.